Aesthetic restoration alternative in the event of dyschromia. Clinical case - Lamas Lara, César (2010)
The restoration of a root canal treated tooth with change of color represents a challenge in the current dentistry, since in some cases it is not enough to perform only one procedure that is the appropriate one in our opinion, but it is possible to consider choosing a set of them to obtain satisfactory results. It is not sufficient to know the forms of the dental pieces if these are not homogenized with the other ones in all their aspects; consequently, the color gains vital importance to perform a good restoration procedure. By applying procedures such as internal and external whitening, as well as composite resins, suitable results can be obtained giving back the patient the aesthetics and function lost. In this article, some basic criteria are detailed to be taken into account in the resolution of a case of dyschromia combining whitening and composite resins procedures; the results obtained were satisfactory since it was possible to provide the patient with the aesthetics and function lost. It is concluded that the appropriate use of these materials as well as the deep knowledge of the techniques lead the success in the resolution of these cases.